Addressing climate-related human mobility through NDCs and NAPs: State of play, good practices, and the ways forward - Mombauer, Dennis; Link, Ann-Christine; van der Geest, Kees (Frontiers in Climate, 2023)
Climate change is altering human mobility patterns across the globe, particularly in climate-vulnerable developing countries. With increasing recognition of the complex interlinkages between climate change and human mobility, governments and subnational authorities have begun to address this nexus in planning and policy processes, including Nationally Determined Contributions (NDCs) and National Adaptation Plans (NAPs). To better understand how human mobility is integrated into NDCs and NAPs, we analysed 171 NDCs and 40 NAPs, and conducted 20 semi-structured interviews and 16 workshops and webinars. We find that human mobility is increasingly featured in NAPs and NDCs, but only few countries propose concrete interventions to address adverse effects or promote adaptive aspects of human mobility. The study also finds that in NAPs and NDCs, human mobility is primarily seen as a risk or a problem. Only few documents promote a balanced view of human mobility by also acknowledging potential positive outcomes (e.g. migration as adaptation). Through six concise case studies, the paper focuses in on good practices from specific NDCs and NAPs that can enhance the integration of human mobility in a range of priority policy sectors for adaptation and loss and damage. To move forward, interviewees and workshop participants emphasized the need for adequate finance, institutional capacities, and data to strengthen the integration of human mobility into NDCs and NAPs. There is a need to identify and better understand potential policy interventions at the local, national, and global level, and to assess their impact and map potential synergies.